Coupling effects of W alloying with preparation temperature on microstructures and irradiation tolerance of nanostructured Cu films. (April 2023) - Mao, Pengyan; Cui, Jingping; Cheng, Zhao; Yang, Lingling; Zhao, Hui; Li, Hongda; Tai, Kaiping
Abstract: Grain size is a critical factor determining materials properties but is challenging to be quantitatively controlled especially in nanoscale. Here, we found the average grain size of pure Cu film can be enhanced from 23 to 557 nm with the preparation temperature increasing from 298 to 773 K during magnetron sputtering. The temperature effect is weakened after W addition to Cu matrix and the grain size of Cu96 W4 samples just exhibits slight increase from 30 to 145 nm. The coupling effect of W alloying with temperature is related to the decreased diffusion of Cu atoms after W addition during magnetron sputtering process. Cu–W supersaturated solid solution is formed at low temperatures (below 773 K for Cu96 W4 or 573 K for Cu94 W6 ) but W atoms could be agglomerated at elevated temperatures. Moreover, after He ions irradiation at 673 K, fewer and smaller cavities are formed in Cu96 W4 samples compared to pure Cu, indicating that W addition could significantly enhance irradiation tolerance. Highlights: Temperature effect on grain growth could be weakened after W alloying. The solute W can accelerate the nucleation while the agglomerated W prefers to stop grain growth. The coupling effect of both temperature and alloying is intrinsically related to the state of W atoms. The addition of W can avoid the severe irradiation damage of Cu films.